Socio-demographic factors influencing abortion practices among women attending Mbagathi Hospital, Nairobi County, Kenya - Okenyoru, Douglas S.; Matoke, Vincent; Wekesa, Claire; Murugi, Lucy; Odhiambo, Felix; J. Kemboi, Sharon (International Journal Of Community Medicine And Public Health, 2024)
Background: Abortion is a global health concern with complex implications, particularly in countries like Kenya, where legal restrictions coexist with prevalent unsafe practices. Despite Kenya's high maternal mortality ratio linked to unsafe abortions, little research has explored the socio-demographic factors influencing this issue. This study investigates these dynamics among women at Mbagathi Hospital in Nairobi County, emphasizing the pressing need for targeted interventions within the legal framework. Methods: A descriptive cross-sectional study was employed. This study focused on women aged 18–49, utilizing a census approach at Mbagathi Hospital's gynecology clinic. The study aimed for 100% precision, resulting in 49 respondents chosen through the purposive sampling method among women aged 18–49 with a history of abortions. Abortion practices were identified as safe and unsafe, and data was collected through a well-structured questionnaire and analyzed using statistical package for the social sciences (SPSS) 22.0. The data was presented in tables and pie charts. Results: The study revealed an unsafe abortion rate of 38.8%. The predictors of abortion practices based on socio-demographic factors were; age (AOR=6.170, p=0.002), marital status (married; AOR=0.438, p=0.025; divorced/widowed/separated; AOR=0.063, p=0.001) and number of children (AOR=0.379, p=0.007). Conclusions: This study revealed that the socio-demographic factors that predicted abortion practices were; age (AOR=6.170, p=0.002), marital status (married; AOR=0.438, p=0.025; divorced/widowed/separated; AOR=0.063, p=0.001) and number of children (AOR=0.379, p=0.007).